Strategi manajemen pendidikan karakter siswa di sekolah dasar unggulan - Rahmatullah Zumaini; Ahmad Suriansyah; Suhaimi Suhaimi (Curricula: Journal of Curriculum Development, 2026)
This study is motivated by the importance of strengthening character education in leading elementary schools to shape students who are noble in character, disciplined, and responsible. This study aims to describe the character education management strategies implemented at SD Negeri 15 Belimbing and SD Negeri 3 Belimbing Raya, Tabalong Regency. This research employed a qualitative approach with a multi-site study design. Data were collected through observation, interviews, and documentation, and then analyzed descriptively. The results show that character education management strategies in both schools are implemented by aligning vision and mission with character values, empowering teachers through continuous training, cultivating character values through routine activities and role modeling, and strengthening school–parent partnerships to support character habituation at home. These findings indicate that the success of character education is determined not only by school programs but also by the synergy of all school members and families. The conclusion of this study emphasizes that collaborative leadership plays a strategic role in achieving character-based excellence in schools.